Primary school children's opportunities and motivations in music: a research in different contexts of music education - Milhano, Sandrina (2021)
This paper examines the perceived and documented opportunities and motivations in music that are available for primary school children’s in different contexts of music education. Through a study of children’s self-perceptions of their participation and learning in the broad range of opportunities that are available to them within music education at Portuguese institutional and cultural levels, four issues are explored: children’s musical activities, both in school and outside school; the influence of children’s participation in extracurricular musical activities at school on their self-assessments of their musical development; changes occurring in children’s musical activities as a function of their participation in extracurricular musical activities, and their attitudes and beliefs about music. The main findings were gathered from two studies that were carried out in two phases (year 1 and 2): the Pupil Questionnaire study (406 children from grades 3 and 4, aged 8-11 years), and the Pupil Interview study. Findings has shown that musical participation in the different contexts of music education seems to be an activity participated in only by a minority of those involved in this research. These contexts include children participation in musical activities both at school as a compulsory subject, and outside school as an elective subject in formal and informal dimensions. Findings suggested that opportunities to participate in music outside school through playing, singing, and dancing activities in the community seem not to be available to many children, with music listening at home remaining as the most common musical activity in which they are involved outside school. One of the strongest indicators of changes occurring in children’s musical activities as a function of their participation in extracurricular musical activities relates to music at school. Across the sample, the children’s level of musical participation in most school activities tended to decrease in frequency in year two. When it existed, the most common musical activity they undertook as part of their statutory music education at school was singing. Most children’s did not participated in many other musical activities at school or outside school before participating in these extracurricular activities. Those seem to provide children with wider opportunities to participate in music, to learn and to develop competences that, as we have seen, are largely neglected by schools. The participation in these extracurricular musical activities seems generating musical development and learning, as well as positively influencing children’s selfassessment of their ‘own musical development’, attitudes and beliefs about music. Most children began enjoying their primary school more with the introduction of these musical activities and evidence supported the fact that taking part in those positively affected these children’s identification with school music lessons as they moved from grade 3 to grade 4. We suggest that the urgency for change in music education in Portugal should be focused more on practices than on attitudes. It seems to be increasingly important not to neglect the importance of nurturing children’s opportunities to actively take part in each one of the potential and desirable contexts of music education, especially music at primary school that should be available to all, not only as a compulsory subject, but also as a reality in the education of all children.